If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12.5 = 38x + 48 Reorder the terms: 12.5 = 48 + 38x Solving 12.5 = 48 + 38x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38x' to each side of the equation. 12.5 + -38x = 48 + 38x + -38x Combine like terms: 38x + -38x = 0 12.5 + -38x = 48 + 0 12.5 + -38x = 48 Add '-12.5' to each side of the equation. 12.5 + -12.5 + -38x = 48 + -12.5 Combine like terms: 12.5 + -12.5 = 0.0 0.0 + -38x = 48 + -12.5 -38x = 48 + -12.5 Combine like terms: 48 + -12.5 = 35.5 -38x = 35.5 Divide each side by '-38'. x = -0.9342105263 Simplifying x = -0.9342105263
| -3(2x+5)=-21 | | 1-5a+9=9 | | (4x^2-3x-11)/(2x-1) | | -6(3+2x)=-126 | | (4X-3)=0 | | 1-5a= | | 7(-5x+2)=-406 | | 6x+12=8x-8 | | .8*.6= | | 4x^2-2x=2 | | -3(-1x+2)=-15 | | .8x.6= | | 9ln-7x=-18 | | 3(4x+2)=-16 | | (x-y)dx+x*dy=0 | | (5X-5)=0 | | 2.2=27.8-8y | | 2(2p+p+3p)-40=24 | | -6(x+4)-41=5-28 | | -9-8y+7x=0 | | 5(-6+2x)=-30 | | X^2-3x=9x | | 4x-28+3x+11=180 | | 2(-6x+1)=134 | | 24-18z+5y=0 | | 3x^3-2x^2-6x+4= | | -4(4-x)=-16 | | -4(6x+3)=24x-12 | | 24x+13=34 | | 3(1x+2)=24 | | -76=8+7x | | (8X+1)(16X-13)=0 |